If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(x + -7) = -10 Reorder the terms: -2(-7 + x) = -10 (-7 * -2 + x * -2) = -10 (14 + -2x) = -10 Solving 14 + -2x = -10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + -2x = -10 + -14 Combine like terms: 14 + -14 = 0 0 + -2x = -10 + -14 -2x = -10 + -14 Combine like terms: -10 + -14 = -24 -2x = -24 Divide each side by '-2'. x = 12 Simplifying x = 12
| .8x+2=.4 | | W=56/(2^2+3) | | g(9)=2x^2+18-14 | | 7n+4(5+2n)=95 | | -5n+4n-7=8 | | -4(8+3n)= | | 0.2t=0.4+0.3t | | 4t+4t= | | 7m-9.4=11.6 | | 1/2t=3.5 | | 5x-(-5x-1)=-8 | | 7x+2=-3+4x+23 | | 11x+2=-24 | | 9v+10=v+9 | | 3.5*2= | | x-19=23 | | 5d+8=53 | | 4x+9-7x=-6 | | 90-x=3/4(180-x)-60 | | 4x+9-7x=-9 | | 0.75=w+2/5 | | (x^2-11)/(2x-1) | | (3/4)x-(7/12)=1 | | 11x-4x=27 | | z/2+1+3/2 | | 3(6x+3)=27 | | 5(2x-4)-(3x+1)=2 | | 9+1/9h=9 | | -6=x/3+4 | | 4x+6+8=3 | | 8(2.4r-3.1s)-6(10-4.3s)= | | x^2+4xy-4y^2-9=0 |